Rapid eye movement (REM) sleep deprivation reduces rat frontal cortex acetylcholinesterase (EC 3.1.1.7) activity - Camarini R.; Benedito M.A.C. (Brazilian Journal of Medical and Biological Research, 1997)
Rapid eye movement (REM) sleep deprivation induces several behavioral changes. Among these, a decrease in yawning behavior produced by low doses of cholinergic agonists is observed which indicates a change in brain cholinergic neurotransmission after REM sleep deprivation. Acetylcholinesterase (Achase) controls acetylcholine (Ach) availability in the synaptic cleft. Therefore, altered Achase activity may lead to a change in Ach availability at the receptor level which, in turn, may result in modification of cholinergic neurotransmission. To determine if REM sleep deprivation would change the activity of Achase, male Wistar rats, 3 months old, weighing 250-300 g, were deprived of REM sleep for 96 h by the flower-pot technique (N = 12). Two additional groups, a home-cage control (N = 6) and a large platform control (N = 6), were also used. Achase was measured in the frontal cortex using two different methods to obtain the enzyme activity. One method consisted of the obtention of total (900 g supernatant), membrane-bound (100,000 g pellet) and soluble (100,000 g supernatant) Achase, and the other method consisted of the obtention of a fraction (40,000 g pellet) enriched in synaptic membrane-bound enzyme. In both preparations, REM sleep deprivation induced a significant decrease in rat frontal cortex Achase activity when compared to both home-cage and large platform controls. REM sleep deprivation induced a significant decrease of 16% in the membrane-bound Achase activity (nmol thiocholine formed min-1 mg protein-1) in the 100,000 g pellet enzyme preparation (home-cage group 152.1 ± 5.7, large platform group 152.7 ± 24.9 and REM sleep-deprived group 127.9 ± 13.8). There was no difference in the soluble enzyme activity. REM sleep deprivation also induced a significant decrease of 20% in the enriched synaptic membrane-bound Achase activity (home-cage group 126.4 ± 21.5, large platform group 127.8 ± 20.4, REM sleep-deprived group 102.8 ± 14.2). Our results suggest that REM sleep deprivation changes Ach availability at the level of its receptors through a decrease in Achase activity